Implementasi Metode Tartil dalam Membaca Al-Qur’an di TPQ Al-Hidayah Jorong Parik Gadang - Nia Putri; Salmiwati Salmiwati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Based on the background of the problem that the author puts forward, namely that the author focuses on the problem as the implementation of the tartil method in reading the Al-Qur’an at TPQ Al-Hidayah Jorong Parik Gadang. This research is a type of qualitative research with a descriptive approach. Implemented at tpq Al-Hidayah Jorong Parik Gadang in August 2023 until completion. The research subjects were teachers and students of tpq Al-Hidayah. The key informant is the techer, the supporting informant is the student. Data collection using interviews, observation, dokumentation. Validity techniques use source triangulary and engineering triangulary. Based on the results of research conducted in the application of reading the Al-Qur’an at tpq Al-Hidayah Jorong parik Gadang using the tartil method, namely effective in reading using the tartil method, in the application process it can be seen that stuudents have practiced how to read the Al-Qur’an well andin reading it they are fluent, true in accordance with the science of tajwid, fashaha, and rhythm, but there are some students who cannot yet because they have holidays, or don’t pay enough attention and pay attention to the teacher, therefore the application of the tartil method in readingthe Al-Qur’an in tpq al Guidance is effective in improving the ability to read the Al-Qur’an